Pembuatan Cairan Pembersih Lantai dengan Memanfaatkan Minyak Atsiri dan Hidrosolnya - Erda Rahmilaila Desfitri; Reni Desmiarti; Sandy Yuda Verdana; Amelia Amanda (Politeknik ATI Padang, 2022)
Floor cleaning products on the market usually use synthetic active that can interfere with health and the environment. Therefore, highly recommended to substitute synthetic active with natural active substances such as essential oils. The by-product of essential oils is hydrosol which is also not safe for the environment. This research aims to analyze hydrosol's effectiveness as an antibacterial and get an optimal formulation of oil essential and hydrosol as antibacterial in floor cleaning products. Kaffir lime leaf oil, lemongrass oil, and its hydrosol have been used as an additive in floor cleaners. pH value, free alkaline level, viscosities, and antibacterial effectiveness have been analyzed for floor cleaning products produced in this research. This research found a pH value of 6-8, viscosities is 1516-1867 cP, and free alkaline level of 0,1519-0,1627 b/b. The most antibacterial effectiveness found in the composition of kaffir lime leaf oil and its hydrosol is 15% and 30%, have bacteria inhibition of 10 mm. pH value, free alkaline, and viscosities have been fulfilled the standard of SNI 1842:2019.